Gender, language and discourse - Weatherall, Ann, 1964- (Women and psychology., 2002)
Is language sexist? Do women and men speak different languages?Gender, Language and Discourse uniquely examines the contribution that psychological research - in particular, discursive psychology - has made to answering these questions. Until now, books on gender and language have tended to be from the sociolinguistic perspective and have focused on one of two issues - sexism in language or gender differences in speech. This book considers both issues and develops the idea that they shouldn't be viewed as mutually exclusive endeavours but rather as part of the same process - the social construction of gender. Ann Weatherall highlights the fresh insights that a social constructionist approach has made to these debates, and presents recent theoretical developments and empirical work in discursive psychology relevant to gender and language. Gender, Language and Discourse provides the most comprehensive and up-to-date discussion of the gender and language field from a psychological perspective. It will be invaluable to students and researchers in social psychology, cultural studies, education, linguistic anthropology and women's studies.